PEMBERDAYAAN MASYARAKAT DALAM MENANGANI HIPERTENSI DI DESA NAMBO KECAMATAN KLAPANUNGGAL - Agustina, Dwi; Sudarsono, Ari; Junisti, Afrilia; Kamila Ghaisani, Grania; Putri Zahraa, Hiliyah; Al-Qahhar, Muhammad Adnan; Adristi, Ratri; Alicia Ariyanto, Salsa (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2025)
Backround: Uninfectious disease, particularly hypertension, have become a significant global health concern. Hypertension is a silent killer that often goes unnoticed until complications arise. Hypertension has risk factors that can be prevented through non-pharmacological approaches, such as health education and physical activity. Community empowerment programs are essential in addressing hypertension through education, lifestyle changes, and physical activities such as aerobic exercise. Objective: This study aims to empower the community in handling hypertension by increasing awareness, knowledge, and physical activity through counseling and low impact aerobic exercise. Method: This activity begins with a door-to-door survey to identify problems, then a pre-tests, health screenings, health education sessions, aerobic exercise training, post-tests, and program evaluation. Results: The program was successful in raising awareness and knowledge about hypertension among the participants, as evidenced by the significant improvement referring to the questionnaire test results. Conclusion: The community physiotherapy program showed a positive impact on hypertension awareness and prevention in Nambo Village. Regular aerobic exercise and continued health education are recommended to sustain the improvements achieved. Further involvement from village leaders and healthcare workers is essential to ensure long-term success. Keywords: Hypertension, Community Physiotherapy, Aerobic Exercise, Public Health, Health Education, Lifestyle Modification.